Near-infrared-persistent luminescence/bioluminescence imaging tracking of transplanted mesenchymal stem cells in pulmonary fibrosis. (29th April 2020) - Xia, Yuyang; Bao, Hongying; Huang, Jie; Li, Xiaodi; Yu, Chenggong; Zhang, Zhijun; Wang, Haishui
Abstract : A dual-labeling strategy integrating near-infrared-persistent luminescence and RfLuc-based bioluminescence imaging techniques has been developed to track the transplanted stem cells, deepening the understanding of the role played by stem cells in PF treatment. Abstract : Human mesenchymal stem cells (hMSCs) are promising in the treatment of pulmonary fibrosis (PF). However, the behavior of hMSCs after transplantation, including dynamic translocation, location and survival, impeding the clinical application of hMSCs in PF is still ambiguous. Herein, we report an effective dual-labeling strategy combining endogenous bioluminescence imaging (BLI) and exogenous near-infrared-persistent luminescence (NIR-PL) imaging for in situ visualization of the transplanted stem cells. The long persistent luminescence nanoparticles (LPLNPs), Zn1.1 Ga1.8 Ge0.1 O4 :Cr 3+, Eu 3+, were developed to track the dynamic translocation, position and distribution of the transplanted hMSCs, taking advantage of their long-lasting NIR-PL imaging ability and minimal autofluorescence background interference. Moreover, in virtue of their ability to express red-emitting firefly luciferase (RfLuc), the living stem cells after transplantation could be discriminated from the dead cells by BLI. This facile pattern contributes to the in situ monitoring of stem cells regarding their spontaneous behavior in vivo and therefore deepening our knowledge in the role played by the transplanted hMSCs in PF therapy.